Risk and protective factors for falls on one level in young children: multicentre case–control study. Issue 6 (13th August 2015) - Benford, P; Young, B; Coupland, C; Watson, M; Hindmarch, P; Hayes, M; Goodenough, T; Majsak-Newman, G; Kendrick, D
Abstract : Background: Childhood falls are an important global public health problem, but there is lack of evidence about their prevention. Falls on one level result in considerable morbidity and they are costly to health services. Objective: To estimate ORs for falls on one level in children aged 0–4 years for a range of safety behaviours, safety equipment use and home hazards. Design, setting and participants: Multicentre case–control study at hospitals, minor injury units and general practices in and around four UK study centres. Participants included 582 children less than 5 years of age with a medically attended fall injury occurring at home and 2460 controls matched on age, sex, calendar time and study centre. Main outcome measure: Fall on one level. Results: Cases' most common injuries were bangs on the head (52%), cuts or grazes not needing stitches (29%) or cuts or grazes needing stitches (17%). Comparing cases to community controls in the adjusted analyses, significant findings were observed for only two exposures. Injured children were significantly less likely to live in a household without furniture corner covers (adjusted OR (AOR) 0.72, 95% CI 0.55 to 0.95), or without rugs and carpets firmly fixed to the floor (AOR 0.76, 95% CI 0.59 to 0.98). Conclusions: We did not find any safety practices, use of safety equipment or home hazards associated with a reduced risk of fall on one level. Our findings do not provide evidence to support changes to current injury prevention practice.